The Development of E-module Teaching Materials for Economics Subjects toward SMA Swasta BPI Paluh Kurau Students - Delima Delima; Kustoro Budiarta; Hasyim Hasyim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The development of teaching materials e-module is an effort to train students to learn independently. This research focused on the feasibility level of developing teaching materials e-module that were applied to class XI students for the 2020/2021 academic year at SMA Swasta BPI Paluh Kurau Hamparan Perak District. A quantitative method was used in this study. The population was all students of class XI at SMA Swasta BPI Paluh Kurau, Hamparan Perak District. To determine the feasibility level, a comparison was made between the experimental class and the control class. The data source results from a questionnaire given to the experimental class to see using e-modules on economic subjects, student test results, and experts. Validation test sheets include e-module design, material experts, and media experts. The procedures and steps of this research used the research model of Borg & Gall (2007: 589), which produces learning products. The result shows that the use of e-modules was in the good or feasible category for use. Overall, learning using e-modules is quite exciting and fun and exciting and easy to use by students. With e-modules, students can become more independent and accelerate learning but still need teacher guidance to have better understand phenomena and language problems in questions in the module.